PENGARUH INFLASI DAN INDEKS PRODUKSI INDUSTRI (IPI) TERHADAP TOTAL EMISI SUKUK KORPORASI DI INDONESIA PERIODE 2014-2018 - Aisyaturrahmah, Auliya Hanifah; Aji, Tony Seno (Jurnal Ekonomika dan Bisnis Islam, 2021)
Sukuk is one of capital market instruments comes as an alternative for investors who want to invest with sharia-compliant and low risk. However, the domestic economy is able to influence the issuance of sukuk, so the further analysis of sukuk by looking at the macroeconomic factors needs to be done. The purpose of this study is to determine the effects of inflation and industrial production index (IPI) on total corporate Sukuk emissions in Indonesia during the 2014-2018 period. The type of this study is quantitative research. The secondary data used are obtained from Bank Indonesia (BI), Badan Pusat Statistik (BPS), and Otoritas Jasa Keuangan (OJK). The results show that inflation has a negative and significant effect. Meanwhile, the industrial production index has a positive and significant effect on total corporate sukuk emissions in Indonesia during the 2014-2018 period